1999
DOI: 10.1038/sj.ijo.0801059
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sibutramine on energy expenditure and appetite during chronic treatment without dietary restriction

Abstract: OBJECTIVE: To assess the contribution of a thermogenic effect to weight loss induced by eight weeks treatment with sibutramine (15mgad) vs placebo in obese subjects. DESIGN: Randomised, placebo controlled, double blind study. SUBJECTS: Thirty-two (7 male, 25 female) healthy obese body mass index (BMI) 33.9 AE 0.5 kgam 2 subjects completed the trial. MEASUREMENTS: Energy expenditure (EE) was measured by indirect calorimetry during a 32 h stay in a respiration chamber before and after 8 weeks treatment. Visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
110
1
7

Year Published

2000
2000
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 25 publications
3
110
1
7
Order By: Relevance
“…The slight increase in systolic blood pressure (5 mmHg) and in diastolic blood pressure (5 mmHg) in the sibutramine group was corroborated by the literature [13][14][15] . The slight increase in blood pressure seems to be compensated by drug-induced weight loss 15 .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The slight increase in systolic blood pressure (5 mmHg) and in diastolic blood pressure (5 mmHg) in the sibutramine group was corroborated by the literature [13][14][15] . The slight increase in blood pressure seems to be compensated by drug-induced weight loss 15 .…”
Section: Discussionsupporting
confidence: 72%
“…Subsequent studies showed a significant effect of the drug on weight loss due to its satietogenic and calorigenic effects [13][14][15] .…”
mentioning
confidence: 99%
“…Part of the effects of sibutramine is due to the inhibition of noradrenaline reuptake with the resulting maintenance of adrenergic tonus in these patients, which can be beneficial for avoiding the drop in energy expenditure that follows weight loss according to the studies by Hansen et al 14 and Seagle et al 15 . This effect, however, could result in an elevation in blood pressure and a reduction in the antihypertensive benefits of weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…The use of sibutramine is associated with an increase in satiety scores and a lack of decline in 24-hour energy expenditure 14,15 , which make sibutramine efficient in inducing weight loss. Several studies show an adequate tolerability profile for the drug; however, aspects referring to hypertensive patients are still inconclusive, and the presence of higher adrenergic activity may interfere with the benefits resulting from weight loss.…”
mentioning
confidence: 99%
“…11,12 Controlled clinical studies have shown that sibutramine produces dose-related weight reduction in obese subjects, as early as 2 weeks after initiation of treatment. 13 However, the norepinephrine activation induced by sibutramine administration could lead to an increase in arterial blood pressure and elevation of heart rate in some patients.…”
Section: Introductionmentioning
confidence: 99%